SISTEM WEB POINT OF SALES (POS) BERBASIS UNIFIED MODELLING LANGUAGE (UML) DENGAN BLACKBOX TESTING UNTUK BARBERSHOP NAGATA - Wisnu Sukma Maulana; Julia Fajaryanti; Aldrick Subhan Zul Hanafi (Jurnal Teknik dan Science, 2024)
Nagata Barbershop has quite a lot of transactions carried out every day, and there are also plans to expand the business by adding branches. Problems arise during this time when recording transactions manually using paper, there is a mismatch with the data that should be used and it is difficult to manage transaction reports. Barbershop Nagata needs an application that can increase the accuracy of recording transactions, make it easier to manage financial reports and can also be used long term if you want to add branches with the same system. The aim of this research is the results of implementing the solutions used to overcome this problem. Choosing a web-based application is a supports for applications that can be accessed any time and can be implemented on different platforms. The Point of Sales (POS) application at the Nagata Barbershop has been tested using black box testing method.